Effect of Drip Irrigation Frequency, N-Fertilization, and Mulching on Yield, Nitrogen, and Water Use Efficiencies of Cucumber (Cucumis sativus L.) in Ikole-Ekiti, Nigeria - Fasina, Abayomi Sunday; Shittu, Olubunmi Samuel; Ogunleye, Kayode Samuel; Ilori, Augustus Oludotun Akinmayowa; Babalola, Temitope Seun (Asian Journal of Agriculture and Rural Development, 2021)
Soil moisture conservation, proper irrigation scheduling and nutrient management are crucial for sustainable cucumber production. A field experiment was set up over two years (2018 and 2019) to investigate the effects of irrigation frequency, black polyethylene mulching, and nitrogen fertilization on cucumber yield, water use efficiency (WUE) and nutrient use efficiency (NUE) at Ikole-Ekiti, Nigeria. The experiment was a 3 x 2 x 2 factorial in a randomized complete block design (RCBD) with a split-plot arrangement and the main plot as drip irrigation frequency: twice per week (I4), three times per week (I5), and four times per week (I6), while the sub-plots were nitrogen fertilization; (no fertilizer, N0 and 180 kg/ha urea, N180) and mulching (no mulch, NM and mulch, M). The highest yield (8.39 and 8.51 t/ha) with the best WUE was obtained from treatment I4MF (F, fertilization), while the lowest (5.81 and 5.79 t/ha) was obtained from I6MF for the respective years. The combination of variables significantly (P<0.05) influenced cucumber yield, WUE, and NUE, and significant correlations were obtained (r=0.87** and 0.85**) between WUE and fruit yield for the study years. The treatment I4MF therefore, could successfully be adopted to reduce water and fertilizer application for improved cucumber yield in the field.